2022
DOI: 10.1371/journal.pone.0264543
|View full text |Cite
|
Sign up to set email alerts
|

Ppe.XapF: High throughput KASP assays to identify fruit response to Xanthomonas arboricola pv. pruni (Xap) in peach

Abstract: Bacterial spot, caused by Xanthomonas arboricola pv. pruni (Xap), is a serious peach disease with symptoms that traverse severe defoliation and black surface pitting, cracking or blemishes on peach fruit with global economic impacts. A management option for control and meeting consumer demand for chemical-free, environmentally friendly fruit production is the development of resistant or tolerant cultivars. We developed simple, accurate, and efficient DNA assays (Ppe.XapF) based on SNP genotyping with KASP tech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…To benchmark PrunusMap, we analyzed relevant markers documented in the literature. For instance, (Fleming et al, 2022) reported two quantitative trait loci (QTLs) linked to fruit resistance to bacterial spot infection (“Xap.PpOC-1.2” and “Xap.PpOC-1.6”), sitting on chromosomes 1 and 6. Eleven SNPs in close proximity to these QTLs were used to design KASP markers, resulting in 44% reduction in seedling planting (Fleming et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…To benchmark PrunusMap, we analyzed relevant markers documented in the literature. For instance, (Fleming et al, 2022) reported two quantitative trait loci (QTLs) linked to fruit resistance to bacterial spot infection (“Xap.PpOC-1.2” and “Xap.PpOC-1.6”), sitting on chromosomes 1 and 6. Eleven SNPs in close proximity to these QTLs were used to design KASP markers, resulting in 44% reduction in seedling planting (Fleming et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…DNA samples for these individuals were obtained using a rapid crude DNA extraction protocol described by Noh et al 43 . The template spreadsheet designed by Fleming et al 23 was employed to automatically assign genotypes. Statistical differences between classes were evaluated using one-way ANOVA, followed by the Tukey test for multiple comparisons in SPSS.…”
Section: Kasp Marker Development and Validationmentioning
confidence: 99%
“…In peach, rapid and accurate DNA tests for predicting bacterial spot severity in fruit and chilling requirement were recently developed 23,24 . Additional tests for peach skin blush 25 , fruit pubescence 26 , subacid trait 27 and esh color 28 are also available.…”
Section: Introductionmentioning
confidence: 99%
“…In peach, rapid and accurate DNA tests for predicting bacterial spot severity in fruit and chilling requirement were recently developed 23 , 24 . Additional tests for peach skin blush 25 , fruit pubescence 26 , subacid 27 and flesh color 28 are also available.…”
Section: Introductionmentioning
confidence: 99%